STRATEGI PROMOSI DINAS PARIWISATA KABUPATEN SIAK DALAM MEMPROMOSIKAN KESENIAN BUDAYA MELAYU MELALUI KEGIATAN SIAK BERMADAH - Reza Listiawan; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In effort to preservation and develop of local art culture, government of Siak Regency through The Tourism Department of Youth and Sport did Siak Praise EventFestival as annual event that had purpose to preservation local art culture, which is held for 14 times, this event can not be denied because management roles and promotion strategy that had rousing in every year that make society and art activists interest to participated in this event.Research methodology that used in this research was kualitative research with a phenomenological approach. There were 2 informants in this research, they were directly handle this activity by using purposive technique. The technique of data collection of this research were interview, observation and documentation. The technique of data analysis were data reduction, data presentation and conclusion and also verification.The result of this research indicate that The Tourism Department of Youth and Sports of Siak Regency in promoting art and malay culture that used structural of goverment function in socialization, that this event was an event of local cultural preservation which its scope was very limited, for Siak Regency only, so that the demand envoy delivered to districts and coaching did the cooperation with the school through the study of art extracurricular, thus breeding envoy takes place on an ongoing basis to the future generations, in used of media is not too published, because this event is only for Siak Regency, so very little or even can be said media not appear in use to publicize the event, in addition to interest of enthusiasts can also be seen from the festive event, the prize for the winners and invited abroad guests to enliven the event, as well as artists of capital to enliven the opening and closing ceremonies.Keywords : Promotion Strategy, Motive, Communication Experience, Art and Culture